A Robotic Gamification Model for Climate Change Literacy for Green Innovation and Entrepreneurship in Sub-Saharan Africa - Oguta, Stephen Ochieng; Ojo, Sunday; Maake, Benard (International Journal of Computing Sciences Research, 2024)
Purpose – The study aims to introduce the Gamified Climate Change Literacy for Green Innovation and Entrepreneurship Training Model, integrating the Social Robot Nao to enhance climate change education in Sub-Saharan Africa. The objective is to empower learners with knowledge about carbon emissions and to foster engagement in green innovations. Method – The model integrates principles from Self-determination theory, Behavioral reinforcement theory, and the Mechanics, Dynamics, and Aesthetics gamification framework. Development and validation were conducted using Design Science Methodology and probability theory. The implementation involves desktop training via Moodle and interactive sessions with the Nao robot. The evaluation is based on the Technology Acceptance Model. Results – The proposed model incorporates random badge awards to enhance engagement and sustain motivation, addressing the shortcomings of traditional reward systems that rely on extrinsic motivation. The integration of the Nao robot adds an interactive element, further increasing learner engagement and interest. Conclusion – The study successfully develops a theoretical framework, mathematical modeling, and architectural design to sustain learner interest in climate change education. By combining gamification with interactive technology, the model redefines educational strategies in this domain. Recommendations – Future implementations should consider scalability and the integration of additional interactive technologies to further enhance engagement. Continuous feedback from learners should be incorporated to refine and improve the model. Research Implications – The study provides a robust framework for utilizing gamification and robotics in educational settings, particularly in regions with limited resources. It opens avenues for further research into the long-term impacts of such models on learner engagement and knowledge retention in climate change education.